Peningkatan Keterampilan Menyelesaikan Masalah Matematika Melalui Model Realistic Mathematic Education pada Peserta Didik Kelas IV Sekolah Dasar Negeri Jomblang 03 Semarang - Darsimah Darsimah (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
This research was conducted to be based on a problem that was considered crucial by the fourth grade teacher namely the mathematical problem. This research is felt to be carried out immediately because students get poor learning outcomes and low classical completeness. Because if left unchecked this problem will continue to the next level. After the researchers made observations, the root cause of the problem was found. Then researchers collaborate with class teachers looking for solutions to solve these problems. Learning with the RME model is chosen to treat existing problems. The learning outcomes of grade IV students of SDN Jomblang 03 Semarang in learning to solve mathematical problems after the RME model has been applied the aspects of skills and aspects of knowledge have increased. The skill aspect gained a 44% percentage of completeness in cycle I, increasing in cycle II 94%. Aspects of knowledge in the first cycle of 44% increased to 67% of the total number of students. It can be concluded that the improvement of research learning through the application of the RME model has been successful because it can improve student learning outcomes.